2016
DOI: 10.1063/1.4943398
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of Williamson fluid flow past a stretching cylinder and heat transfer with variable thermal conductivity and heat generation/absorption

Abstract: In this article, Williamson fluid flow and heat transfer over a stretching cylinder is discussed. The thermal conductivity is assumed to be vary linearly with temperature. Heat generation/absorption effects are also taken into account. Modeled partial differential equations are converted into ordinary differential form by using appropriate transformations. Shooting method in conjunction with Runge-Kutta-Fehlberg method is used to find the solution of the problem. Moreover, the effects of different flow paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 23 publications
3
54
0
Order By: Relevance
“…It is conspicuous from Figure 6 that, as the ω accelerates, the fluid velocity annihilates. The aftermaths conceived for ω on velocity field in this dissertation is in an excellent bargain with the evaluated upshots of Nadeem et al [21], Hayat et al [22], Malik et al [23]. Williamson parameter, ω, has a little influence on the nanofluid velocity; however, the velocity tendency has never been changed.…”
Section: Upshots and Argumentmentioning
confidence: 59%
See 1 more Smart Citation
“…It is conspicuous from Figure 6 that, as the ω accelerates, the fluid velocity annihilates. The aftermaths conceived for ω on velocity field in this dissertation is in an excellent bargain with the evaluated upshots of Nadeem et al [21], Hayat et al [22], Malik et al [23]. Williamson parameter, ω, has a little influence on the nanofluid velocity; however, the velocity tendency has never been changed.…”
Section: Upshots and Argumentmentioning
confidence: 59%
“…In contrast, the investigation associated with the pseudoplastic Williamson fluid on a stretched surface was carried out by Nadeem et al [21], where the velocity was observed portraying a descending trend owing to the rising value of Williamson parameter. Following the recent practice, the Williamson fluid model, with the assistance of various flow diagrams, was adequately probed by these authors [22][23][24]. It is obvious to be briefly mentioned that Williamson fluids are effectively employed in numerous industrial purposes like food mixing and to analyse the chime movement in the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Consider a steady, incompressible, three dimensional axisymmetric flow of Williamson fluid over a rotating disk with heat and mass transfer. The flow is produced by a disk with anisotropic slip rotating infinitely with constant angular velocity  , extended infinitely in 6 the positive half-space of the disk   0  z and initially placed at 0  z . A uniform external magnetic field of strength 0 B is applied normal to the disk.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Malik, et al [5] presented Keller box solution of the homogeneous-heterogeneous reactions on Williamson fluid over a stretching cylinder. Recently, Malik, et al [6] have numerically investigated the effects of variable thermal conductivity and heat generation/absorption on Williamson fluid flow and heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable consideration has been given to investigate the characteristics of heat transmission mechanism. Many authors [13][14][15][16][17] have utilized the experiential law of heat transfer recognized as Fourier's law. In the last two centuries, Fourier's law was found to be satisfactory for describing the heat transfer phenomenon.…”
Section: Introductionmentioning
confidence: 99%